Charging mechanism in a SiO2 matrix embedded with Si nanocrystals - Fu, Yong Qing (2010)
One of the applications of a Si nanocrystals (nc-Si) embedded in a SiO2 matrix is in the area of nonvolatile memory devices based on the charge storage in the material system. However, whether the charge trapping mainly occurs at the nc-Si/SiO2 interface or in the nc-Si is still unclear. In this work, by x-ray photoemission spectroscopy analysis of the Si 2p peaks, the concentrations of both the nc-Si and the Si suboxides that exist at the nc-Si/SiO2 interface are determined as a function of thermal annealing, and the charging effect is also measured by monitoring the shift of the surface C 1s peak. It is observed that the annealing-caused reduction of the total concentration of the interfacial suboxides is much faster than that of both the C 1s shift and the nc-Si concentration. In addition, the trend of the C 1s shift coincides with that of the nc-Si concentration. The results suggest that the Si nanocrystal, rather than the nc-Si/SiO2 interface, plays the dominant role in the charging effect.